2009
DOI: 10.1080/03009740802642062
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer among patients with systemic sclerosis in Korea: results from a single centre

Abstract: The SIR of cancer was significantly higher in SSc patients, and especially in those who were male, than in the general population. Lung cancer was the most common cancer. Active surveillance for the detection of cancer should be performed in all SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…Some studies reported no significant increased risk (19)(20)(21), similar to our results, while other studies indicated an excess incidence of malignancy with significantly increased SIRs (22)(23)(24)(25)(26)(27)(28)(29)(30). In SSc patients with long disease duration, it is not rare to develop a malignancy with or without carcinogenic effect of SSc itself or the medication, such as cyclophosphamide.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies reported no significant increased risk (19)(20)(21), similar to our results, while other studies indicated an excess incidence of malignancy with significantly increased SIRs (22)(23)(24)(25)(26)(27)(28)(29)(30). In SSc patients with long disease duration, it is not rare to develop a malignancy with or without carcinogenic effect of SSc itself or the medication, such as cyclophosphamide.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the histopathological type of lung cancer was characterized as predominant adenocarcinoma (including bronchioloalveolar carcinoma), which has often been reported to be the most frequent type (24,27,29,34). Similarly, adenocarcinoma was the most common type in nonSSc Japanese patients with ILD (36), as well as in the Japanese general population, especially in females (41).…”
Section: Discussionmentioning
confidence: 90%
“…While the data are controversial, some studies have suggested that the risk of cancer may be higher in patients with diffuse cutaneous disease (4). Similarly, interstitial lung disease may be a risk factor for lung cancer in scleroderma (1, 14, 15). Patients developing new onset scleroderma at an older age also have an elevated risk of cancer (see details below) (1, 16, 17).…”
Section: Scleroderma Patients Have An Elevated Risk Of Many Types Of mentioning
confidence: 99%
“…The majority of patients with scleroderma who develop lung cancer have underlying interstitial lung fibrosis, are female and the most frequent tumors are adenocarcinoma or of the bronchioloalveolar cell type [169] , not necessarily associated with cigarette smoking [163] . The average interval time between the onset of these two diseases appears to be more than 5 years [163,[170][171][172] . It is believed that the chronic inflammation and repair that occur in SS-ILD results in recurrent cellular injury and genetic damage to local epithelial cells, predisposing to the development of cancer through sequential cellular morphological alterations [173] .…”
Section: Ss and Lung Cancermentioning
confidence: 99%